Analysis of Acceleration Construction Project the Lecture Building at Politeknik Negeri Madura Using the Time Cost Trade off Method - Dimas Fitra Herkunadi; Budi Witjaksana (Publikasi Indonesia, 2025)
This study investigates the effectiveness of Social Media Marketing Activities (SMMA) on purchase intention, using Fitfuel as a case study. The research examines the impact of SMMA on brand awareness and customer trust, and how these two variables influence purchase intention. A quantitative approach was employed, using online questionnaires distributed to 200 respondents, supported by interviews with Fitfuel's management. The external and internal environment were analyzed through PESTEL, Porter’s Five Forces, competitor analysis, STP, Marketing Mix, VRIO, and SWOT. Results show that SMMA has a significant positive effect on both brand awareness and customer trust. In turn, both brand awareness and customer trust positively influence purchase intention. However, communication between consumers and the brand (as part of SMMA) was found to have a less significant effect compared to other indicators. The study presents a TOWS matrix and implementation plan to offer strategic actions for Fitfuel to optimize its digital marketing, strengthen brand perception, and increase conversion. This research contributes to understanding how digital marketing components affect customer behavior in the health food sector.